Education expansion and income distribution in the Philippines - Alvarez, Julian Thomas B.; Daway-Ducanes, Sarah Lynne S. (Quezon City School of Economics, University of the Philippines Diliman, 2020)
This paper examines how education expansion, in terms of increasing the average years of schooling, influences inequality and the distribution dynamics of income in the Philippines, by employing the decomposition method proposed by Firpo, Fortin and Limieux (2009) on household-level data from the 2004 and 2014 Annual Poverty Indicators Surveys. The findings suggest that the effect of a given expansion in the average years of schooling on income inequality may differ depending on how this is achieved: While basic education expansion increases the share of the lower income groups (thereby reducing income inequality), tertiary education expansion significantly raises inequality, as it disproportionately raises the shares of the richest decile. Education expansion also indirectly affects income inequality by affecting the probability of the household’s participation in agricultural activities, wholesale and retail trade and other sources of income. Finally, decomposing the effects of education expansion into its price and structure effects allows us to delve into the effects of education expansion on the distribution dynamics of overall income and wage earnings between 2004 and 2014. In terms of the overall income distribution, the structure effect accounts for a sizeable proportion of the observed increase in income inequality, while the price effect is insignificant. In terms of wage distribution, however, the price effect of education contributed to an increase in the wage earnings gap, as unskilled labor is placed at a disadvantage as a result of skill-biased technological change. These results shed some light on the potential distributional effects of recent education reforms institutionalized in the Philippines.
Thesis (M.A. Economics) -- University of the Philippines Diliman
Keywords: Economic development -- Effect of education on -- Philippines; Income distribution -- Social aspects -- Philippines